Friction torque in four-point contact slewing bearings: Applicability and limitations of current analytical formulations. (November 2017) - Heras, Iker; Aguirrebeitia, Josu; Abasolo, Mikel; Plaza, Jon
Abstract: The friction torque is a key parameter in the design of slewing bearings. The most challenging issue in its calculation resides in the modelling of rolling element contact mechanics. In this manuscript two models for the friction torque calculation are compared: a Finite Element model and the analytical model proposed by Leblanc and Nelias. The last one assumes that full sliding occurs in the ball-raceway contact, which is demonstrated to be an appropriate simplification for many cases, but not for applications where large tilting moments are involved. The objective of this work is to determine the field of application of the analytical model, highlighting its limitations and therefore justifying further research to implement more complex formulations for the contact simulation. Highlights: Accurate bolt raceway contact models are needed to calculate friction torque. State of the art contact models assume full sliding contact. This work proves that large stick regions exist in typical applications. This work proves that full sliding assumption may lead to inaccurate torque results. It is concluded that improved contact models must be developed.